The sensitivity of failure analysis of boiler tubes to the shape of elliptical external erosion flaws. (January 2021) - Kalu, Ifeanyi Emmanuel; Inglis, Helen Mary; Kok, Schalk
Highlights: Geometric functions to enable the accurate modelling of boiler tubes with localized erosion flaws were developed. Effect of the flaw geometries on the stress concentrations and failure pressures of the tubes were investigated. Failure of the tubes is insensitive to the choice of flaw shape, as long as the minimum remaining tube thickness is matched. For various failure criteria thresholds, failure assessment of flawed tubes is fairly insensitive to their flaw shapes. Abstract: Localized erosion is one of the most common failure mechanisms associated with boiler tubes, driven by impaction of the tube surface by fly ash, soot blowing steam, falling slag or other abrasive substances from the boiler's combustion chamber. The tubes may experience significant localized reduction in their wall thickness, becoming susceptible to plastic collapse and bursting. The replacement of failed tubes is one of the leading causes of unplanned and forced boiler outages in process and power plants. In this study, geometric functions to enable the accurate modelling of boiler tubes with localized erosion flaws were developed from conceptualized models and finite element analyses were conducted on the modelled flawed tubes. The effect of geometry on the stress concentration in the tubes and on the failure pressure associated with the tubes was investigated. Linear elastic stress analysis is sensitive to the flaw geometry – for a representative problem stresses vary 38% as the flaw shape is varied. However, nonlinear elastic-plastic analysis shows significantly reduced sensitivity to flaw shape. The collapse pressure of the same representative problem now varies only 2.45% as the flaw shape is varied. This finding was demonstrated for various failure thresholds sourced from the literature, based either on plastic strain or Von Mises equivalent stress, which demonstrates that the failure of the tubes is insensitive to the specific choice of shape parameterization, as long as the minimum remaining wall thickness is matched. The outcome of these investigations gives further insight into the behaviour of tubes with localized external flaws while in service.